2012
DOI: 10.1523/jneurosci.1361-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Spike Resonance Properties in Hippocampal O-LM Cells Are Dependent on Refractory Dynamics

Abstract: During a wide variety of behaviors, hippocampal field potentials show significant power in the theta (4–12 Hz) frequency range and individual neurons commonly phase-lock with the 4–12 Hz field potential. The underlying cellular and network mechanisms that generate the theta rhythm, however, are poorly understood. Oriens-lacunosum moleculare (O-LM) interneurons have been implicated as crucial contributors to generating theta in local hippocampal circuits because of their unique axonal projections, slow synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 60 publications
4
74
0
Order By: Relevance
“…PVBCs fire fast, nonaccommodating action potentials and have fast membrane time constants, and GABA-release from their axon terminals takes place in a synchronous manner with tight temporal association between the presynaptic action potential and the postsynaptic response (38,39). OLM cells receive their primary, markedly facilitating excitatory inputs from local CA1 pyramidal cells with minimal input from CA3 pyramidal cell axon collaterals (40,41), and their intrinsic biophysical properties are thought to enable them to participate preferentially in theta-frequency activity (42)(43)(44)(45)(46). Therefore, by focusing on PVBCs and OLM cells, the present study aimed to determine the temporal structure of spiking activity of two key sources of perisomatic and distal dendritic GABAergic input to CA1 pyramidal cells under anesthesia-free conditions and across a range of network oscillatory frequencies spanning a wide range from <10 Hz to >100 Hz, with four specific frequency bands associated with distinct behavioral states and functions.…”
Section: Discussionmentioning
confidence: 99%
“…PVBCs fire fast, nonaccommodating action potentials and have fast membrane time constants, and GABA-release from their axon terminals takes place in a synchronous manner with tight temporal association between the presynaptic action potential and the postsynaptic response (38,39). OLM cells receive their primary, markedly facilitating excitatory inputs from local CA1 pyramidal cells with minimal input from CA3 pyramidal cell axon collaterals (40,41), and their intrinsic biophysical properties are thought to enable them to participate preferentially in theta-frequency activity (42)(43)(44)(45)(46). Therefore, by focusing on PVBCs and OLM cells, the present study aimed to determine the temporal structure of spiking activity of two key sources of perisomatic and distal dendritic GABAergic input to CA1 pyramidal cells under anesthesia-free conditions and across a range of network oscillatory frequencies spanning a wide range from <10 Hz to >100 Hz, with four specific frequency bands associated with distinct behavioral states and functions.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies in recent years has focused on subthreshold membrane resonance in neurons, its dependence on ionic currents and its influence on neuronal and network oscillations (Richardson et al 2003; Ledoux and N. 2011; Castro-Alamancos et al 2007; Tohidi and Nadim 2009; Izhikevich et al 2003; Engel et al 2008; Reinker et al 2004; Kispersky et al 2012; Moca et al 2012; Thevenin et al 2011). Subthreshold membrane resonance is primarily described on the basis of a linear RLC circuit where R is equated with the membrane resistance, C with the membrane capacitance and the inductance L , more abstractly, with voltage-gated ionic conductance properties (Erchova et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SOM Interneurons Modulate TA Inputs SOM interneurons have long been foreseen as instrumental in hippocampal theta generation (Gloveli et al, 2005) (but see Kispersky et al, 2012). In addition, recent work has demonstrated that SOM interneurons influence the probability of PC burst firing (Lovett-Barron et al, 2012;Royer et al, 2012).…”
Section: Pv and Pc Network Are The Basic Units Of Dca1/sub Intrinsicmentioning
confidence: 99%